TRANSFORMASI PROFESIONALISME PEGAWAI MELALUI PRAKTIK KOMUNIKASI BISNIS DI ERA DIGITAL - Irawan, Dedi; Putra Aji, Gatot Bintoro (STMIK Pringsewu, 2025)
This study aims to analyze how business communication practices in the digital era transform employee professionalism within micro, small, and medium enterprises (MSMEs), using a case study of JJ Shop Sukarame, Bandar Lampung. The research employs a qualitative approach with a case study method through in-depth interviews, participatory observation, and documentation, analyzed using the Miles and Huberman model. The findings indicate that the implementation of digital business communication through platforms such as WhatsApp and Instagram significantly enhances employee professionalism. Digital communication improves coordination, strengthens discipline and responsibility, and fosters open relationships between owners, employees, and customers. These results reinforce Katz and Kahn’s organizational communication theory and Spitzberg and Cupach’s communication competence model, emphasizing clarity, ethics, and communication skills in shaping professional behavior. The study contributes theoretically to the development of digital business communication concepts within MSMEs and provides practical implications for cultivating a professional work culture in the era of technological transformation